The Relationship between Knowledge and Mother's Attitude towards Exclusive Breastfeeding in the Independent Practice of Midwife Indah Suryawati Kel. Sumber Karya Timur Binjai District in 2020 - Siskawati Amri (Institute of Computer Science (IOCS), 2020)
Breast milk has advantages and privileges as a nutrient compared to other nutritional sources. The macro and micro components contained in breast milk are very important needed at every stage of the baby's growth. Objectives To determine the relationship between knowledge and mother's attitude towards exclusive breastfeeding in the independent practice of Midwife Indah Suryawati Kel.Sumber Karya Timur Binjai District in 2020. Results There is a relationship between mother's attitude towards exclusive breastfeeding in the Independent Practice of Midwife Indah Suryawati Kel.Sumber Karya Binjai District East Year 2020. Obtained by calculating the chi-square statistical test with df = 1 p value = 0.001 < 0.05.